Bivalirudin used as alternative anticoagulant in carotid artery stenting: a single center observational study - Geisbüsch, Philipp (Journal of vascular and interventional radiology, 2012)
Purpose: To analyze and report the safety and effectiveness of bivalirudin in a large patient population undergoing carotid artery stenting (CAS). Methods: Between January 2001 and November 2010 extracranial CAS was performed in 272 patients in our institution. These patients were stratified according to the anticoagulant used during the CAS procedure into 2 groups (bivalirudin n = 217 vs. unfractionated heparin [UFH] n = 55) and analyzed regarding bleeding complications and periprocedural (within 30 days) stroke and myocardial infarction (MI) rates. Results: The combined end-point of death, stroke, and MI occurred in 12 patients (4.4%) with no significant difference between the groups (bivalirudin 4.6% vs. UFH 3.6% P value 0.96). Stroke rates were 1.8% in the bivalirudin and 1.8% in the UFH group (P value 1.00), with 4/5 strokes being nondisabling. Periprocedural MI was observed in 7 patients (2.1%) with no significant differences between the groups (bivalirudin 2.7% vs. UFH 1.8%, P value 0.94). Bleeding complications occurred in 13/272 patients (4.7%) with no significant difference between the groups (bivalirudin 3.6% vs. UFH 9.0%, P value 0.15). The first activated clotting time after administration of the anticoagulants was therapeutic in 209/217 (96%) in the bivalirudin group and in 30/55 (55%) in the UFH group (P < 0.001). Conclusions: In this single-center study, bivalirudin was a safe and efficient anticoagulation strategy for CAS and could be considered a therapeutic alternative to UFH. (J Interven Cardiol 2012;25:197-202)